Clock-Drawing in Neurological Disorders - Gerald Dal Pan; Yaakov Stern; Mary Sano; Richard Mayeux (Behavioural Neurology)
Clock-drawing is a widely used bedside test of constructional ability, but it has never been systematically studied or standardized. We examined 87 clocks drawn by neurologically impaired patients and age-matched controls, and propose a set of criteria for scoring clocks. Patients with probable Alzheimer's disease and other dementias have gross impairments in clock-drawing. These deficits include poor spatial arrangement of numbers, incorrect numerical sequence, insertion of stray lines, and addition of extra numbers. In Alzheimer's disease, the total score on the clock-drawing test correlates with the score on the Modified “Mini-Mental State” Examination. Non-demented patients with Parkinson's disease showed only defects in the spatial organization of the numbers, and non-demented patients with other diseases perform as well as controls.